If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2l + 4) = 112 Reorder the terms: 8(4 + 2l) = 112 (4 * 8 + 2l * 8) = 112 (32 + 16l) = 112 Solving 32 + 16l = 112 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + 16l = 112 + -32 Combine like terms: 32 + -32 = 0 0 + 16l = 112 + -32 16l = 112 + -32 Combine like terms: 112 + -32 = 80 16l = 80 Divide each side by '16'. l = 5 Simplifying l = 5
| 3b*b-18b+30=0 | | 4x-2(-3x-7)=-10-6x | | (a-5)=36 | | 10v^2-27v+5=0 | | -a/5=1/5 | | (x+3)(x+1)=4x+7 | | 2x^2+4x=621 | | t^2+4t+4=7 | | -5k=-14 | | 8x+3=4x+3 | | (u+1)*10=40 | | (q-10)*5=50 | | 5+3r=5 | | 2-2x/5=x-6 | | x^2+6x=120 | | 7x+3=19+5x | | 8y-2=14y-4 | | b=1/3=2 | | X^2+6x+33=0 | | (-4e^-2x)/(e^-5x) | | 16-3x=-7x+12 | | 5a^2-21a+18=0 | | 2/3a^2=23 | | 6x-10=-20 | | 14fa-72a^2+f^2= | | 2/3g=6=-12 | | -5z+6=6z-38 | | 144=-12(X+-60) | | a*bcd=bcd*a | | 1X+8=3X+14 | | (x+y)=3(x+y)-2 | | 4x-(3x-7)-(2x-3)=8x(x-1) |